Matrix Theory on Lorentz-Minkowski Scalar Product - Marangoz, A.; Yuce, S. (INST MATH & MECHANICS AZERBAIJAN, 2024)
In this paper, we investigate Lorentz-Minkowski matrix multiplication introduced in [3] by O. Kecilioglu and H. Gundogan. Unlike [3], we will define some transformations to get a connection between Lorentz-Minkowski matrix multiplication and Euclidean matrix multiplication which allows for a more practical use instead of direct approach.
Keywords: pseudo matrix multiplication; isomorphism; Mathematics